Factors associated with needlestick injuries among healthcare workers: implications for prevention - Kifah Habib Alfulayw; Sultan T. Al-Otaibi; Hatem A. Alqahtani (BMC Health Services Research, 2021)
Abstract Background Our study sought to determine the frequency of Needlestick injuries (NSIs) among Healthcare Workers (HCWs) working at governmental hospital and to study the factors that associated with occurrence of NSIs, and to develop recommendations for a comprehensive program for prevention. Methods Retrospective study of all reported cases of NSIs in the period from April 2016 to May 2018 among healthcare workers at a governmental hospital. Results Incidence of NSIs over 26 months was 8.4% among all participants. Nurses were the most affected staff (52.5%) resulted commonly from disposing syringes (58.9%). In contrast, the incidence of NSIs among physicians was 24.9% where surgical devices were the primary source of NSIs among them (40%). Failure to complete all required hepatitis B vaccination was common among expatriates of the participants of this study. Conclusions NSIs was common among HCWs participated in this study. Preventive measures should be implemented including adequate hepatitis B immunization.